Temporal order of cancers and mental disorders in an adult population. Issue 3 (19th April 2018) - Cawthorpe, David; Kerba, Marc; Narendran, Aru; Ghuttora, Harleen; Chartier, Gabrielle; Sartorius, Norman
Abstract : Background: Population-based examination of comorbidity is an emerging field of study. Aims: The purpose of the present population level study is to expand our understanding of how cancer and mental illness are temporally associated. Method: A sample of 83 648 056 physician billing records for 664 838 (56% female) unique individuals over the age of 18 was stratified on ages 19–49 years and 50+ years, with temporal order of mental disorder and cancer forming the basis of comparison. Results: Mental disorders preceded cancers for both genders within each age strata. The full range of cancers and mental disorders preceding or following each pivot ICD class are described in terms of frequency of diagnosis and duration in days, with specific examples illustrated. Conclusions: The temporal comorbidity between specific cancers and mental disorders may be useful in screening or clinical planning and may represent indicators of disease mechanism that warrant further screening or investigation. Declaration of interest: None.